2011
DOI: 10.2139/ssrn.1549668
|View full text |Cite
|
Sign up to set email alerts
|

Limits to Arbitrage During the Crisis: Funding Liquidity Constraints and Covered Interest Parity

Abstract: Arbitrage normally ensures that covered interest parity holds. Yet, this paper shows that this central condition in finance broke down for several months after the Lehman bankruptcy for trades funded in dollars. This anomaly emerges for two popular arbitrage strategies, using both unsecured and secured funding. The secured strategy, newly investigated in this paper, avoids default and rollover risks, thus favoring funding liquidity constraints as an explanation for arbitrage deviations. Additional empirical te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 51 publications
(15 reference statements)
2
13
0
Order By: Relevance
“…Not surprisingly, considering that Mancini Griffoli and Ranaldo (2012) and others have found liquidity to be an important driver of currency fluctuations during the global financial crisis, we find some significant liquidity effects, most notably that the CHF tends to depreciate against the USD as liquidity in the CHF/USD market increases, but only when uncertainty is relatively low (i.e. below the endogenously identified threshold).…”
Section: Robustnesssupporting
confidence: 47%
“…Not surprisingly, considering that Mancini Griffoli and Ranaldo (2012) and others have found liquidity to be an important driver of currency fluctuations during the global financial crisis, we find some significant liquidity effects, most notably that the CHF tends to depreciate against the USD as liquidity in the CHF/USD market increases, but only when uncertainty is relatively low (i.e. below the endogenously identified threshold).…”
Section: Robustnesssupporting
confidence: 47%
“…First, we show that stock market efficiency, rather than being a static concept, exhibits significant variation over time, and that different efficiency measures comove across individual stocks, as well as with each other. Second, we note that while prior work has studied the link between funding liquidity and market liquidity (e.g., Brunnermeier and Pedersen 2009;Hameed, Kang, and Viswanathan 2010), and between funding liquidity and specific arbitrage strategies in convertible bonds, mergers, covered interest parity, credit default swaps, and closed-end funds (e.g., Mitchell, Pedersen, and Pulvino 2007;Gârleanu and Pedersen 2011;Mancini-Griffoli and Ranaldo 2011;Mitchell and Pulvino 2012), our study demonstrates a connection between funding liquidity and the systematic component of commonly accepted efficiency measures for equities. Our results suggest that policy attempts to increase funding liquidity may not only have a direct impact on trading costs but also have an impact on the systematic degree of stock price efficiency.…”
mentioning
confidence: 58%
“…For example, Sack (2010) discussed how the emergency liquidity provision facilities including the Term Asset Backed Securities Loan Facility (TALF) revitalized transactions in the securitized credit markets, and Mancini-Griffoli and Ranaldo (2010) showed that cross-border money market arbitrage opportunities were restored as soon as the exchange swap lines were established. Krishnamurthy and Vissing-Jorgensen (2010) estimated that QE1 decreased MBS yields by 150 basis points, and Hancock and Passmore (2011) estimated that its effect on the mortgage rate was almost 50 bps.…”
Section: Quantitative Easing Of the Usmentioning
confidence: 99%